1975
DOI: 10.1159/000117498
|View full text |Cite
|
Sign up to set email alerts
|

The Common Pathophysiology of Monoaminergic Psychoses: a New Hypothesis

Abstract: Several recent data indicate the blood-brain transport of amino acids as a critical factor in the synthesis of monoamines. The complex, peripheral and central regulation of TP transport plays an essential role since TP-hydroxylase is not a saturated enzyme. The hydroxylated derivatives 5-HTP and dopa are probably transported into the brain by similar mechanisms as their precursors TP and tyrosine, respectively. The manic-depressive patients show an increased uptake of administered L-5-HTP in the depressive pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

1978
1978
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 26 publications
(28 reference statements)
0
22
0
2
Order By: Relevance
“…Anyway, our results could also tend to favor the etiologic hypotheses which privilege qualitative aspects ex pressed in terms of dysregulation [Siever et al, 1985] or imbalance of monoaminergic systems [Tissot, 1975]. Further, one tends to assume the general assumption that a depression episode must be treated, after improve ment, for a sufficiently long time to prevent relapse.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Anyway, our results could also tend to favor the etiologic hypotheses which privilege qualitative aspects ex pressed in terms of dysregulation [Siever et al, 1985] or imbalance of monoaminergic systems [Tissot, 1975]. Further, one tends to assume the general assumption that a depression episode must be treated, after improve ment, for a sufficiently long time to prevent relapse.…”
Section: Discussionmentioning
confidence: 53%
“…According to the presumed role of amino acid transport devoted to erythrocytes [Felig et al, 1973;Christensen, 1982], it is difficult to consider the only measurements of plasma levels without under estimating the underlying dynamic processes. So, these abnormalities may focus on relations between availabil ity of monoamine precursors and neurotransmitter brain functions [Wurtman and Fernstrom, 1972], despite con troversy [De Feudis, 1987], This is of importance be cause these brain neurotransmitters and their precursors have been implicated in the etiology of affective disor ders [Tissot, 1975;Gaillard and Tissot, 1979], Little is known about these mechanisms of transport. Concern ing erythrocytes, System L exhibits a reactivity towards LNAA, in particular TYR, PHE and in most part of free TRP (only less than 10% is transported by human eryth rocyte System T).…”
Section: Discussionmentioning
confidence: 99%
“…Monoamines as well as their precursors, the amino acids ¿-tyrosine (TYR) and ¿-tryptophan (TRP), have been implicated in biological mechanisms of mood dis orders [Wurtman and Fernstrom, 1972;Tissot, 1975;Coppen and Wood, 1978;Möller et al, 1983], Prelimi nary studies have measured the arteriovenous differ ences of these two amino acid concentrations: the blood transport of TYR to the brain was reduced in depressed patients whereas transport of TRP was increased. More over a close relationship was observed between the blood-brain barrier and plasma red cell transport of TRP (r = 0.946, p < 0.01) [Tissot et al, 1978;Gaillard and Tissot, 1979;Tissot, 1984], This observation brought us to use the red cell membrane as a peripheral model to further investigate the transport mechanism of these two amino acids [Widmer et al, 1982], In a previous study we showed that in depressed bipo lar subjects (DSM III criteria: 296.5 x), erythrocyte mem brane transport (MT) of TYR was significantly lower than in normal subjects (p < 0.001), and MT TRP remained within the normal range.…”
Section: Introductionmentioning
confidence: 99%
“…Rappelons que, pour la psychose maniaco-dépressive, quatre hypothèses concurrentes ou complémentaires ont cours: sérotoninergique (2); catécholaminergique (9,10); rapport sérotonine/ catécholamines augmenté (13) et ionique (3,4). Pour la schizophrénie, deux hypothèses complémentaires semblent solides: dopaminergique (12) et rapport dopamine/sérotonine augmenté (11,13). L'un de nous (13) a proposé la synthèse suivante: les perturbations des métabolismes rappelées ci-dessus pour raient être corrélées à des modifications de la capture par le cerveau du trypto phane et de la tyrosine circulants.…”
Section: Introductionunclassified
“…Si l'on admet que le 5-HTP et la ¿-dopa sont très probablement transportés par le même système que le tryptophane et la tyrosine (7) et que la production de 5-HT et de DA, à partir du ¿-5-HTP et de la /.-dopa, qui ont pénétré dans le cerveau, n'est pas limitée par l'étape de l'hydroxylation, on peut attendre qu'une perfusion de ¿-5-HTP ou de ¿-dopa, tant par compétition directe au niveau des mécanismes de transport que par régulation rétroactive de ces derniers sous l'effet de la production, dans le cerveau, de 5-HT et de DA, provoque des modifications importantes de la capture du tryptophane et de la tyrosine endogènes (13). Ce travail, mené conjointement par le Service de Psychiatrie de l'Institut national de Neurologie de Mexico et de la Clinique universitaire de Psychiatrie de Genève, constitue un premier essai de vérification de ce modèle.…”
Section: Introductionunclassified